Severe aortic stenosis in elderly patients. Issue 5 (May 1986) - Nylander, E; Ekman, I; Marklund, T; Sinnerstad, B; Karlsson, E; Wranne, B
Abstract : Clinical and non-invasive findings were compared with catheterisation data in 91 elderly patients (mean 65 years, range 52-78) with suspected severe aortic stenosis requiring operation. Heart catheterisation showed that forty nine patients had a valve area of less than or equal to 0.6 cm2, 36 had a valve area of 0.7 - 1.0 cm2, and six an area of greater than or equal to 1.1 cm2. Coexistent aortic regurgitation was found in 85% of the cases, but severe regurgitation was found in only one patient (1%). Seventy seven per cent of patients had chest pain, 74% had dyspnoea, and 46% had exertional vertigo or syncope. Coronary angiography, which was performed in 77 patients, showed coronary artery disease in 24% of those with a history of angina pectoris and in none of those without. All patients had echodense valves; aortic valve calcification was shown by x ray in 76% and in all but one by cineradiography. The peak of the systolic murmur was delayed in 98% of the patients. Although a prolonged left ventricular ejection time was characteristic of severe aortic stenosis, a normal value did not exclude this diagnosis. Most patients (84%) had increased QRS amplitude on the electrocardiogram. Echocardiography showed an increased left ventricular wall thickness in 90% of the patients in whom it was possible to define the myocardial borders. There was an inadequate blood pressure increase in response to exercise in 82%. In about 25% of the patients the exercise test was at variance with the New York Heart Association classification. Findings suggesting severe aortic stenosis resembled those reported for younger age groups. When most findings point to severe aortic stenosis, the absence of a single symptom or non-invasive sign does not exclude severe aortic stenosis.